Protective effects of resveratrol and naringenin against nonylphenol-induced oxidative stress in rats - Haitham S. Elewa; Dawlat A. Salama; Mohamed S. Hikal; Mohamed F. Abd El hamid; Mohamed H. Eid; Fatma M. A. Khalil; Muayad S. Albadrani; Khaled Abdelaal; Ahmed I. El-Tokhy (AMB Express)
Abstract Nonylphenol (NP) is a ubiquitous environmental endocrine disrupting chemical and oxidative stress inducer in biological systems. Resveratrol (RES) and Naringenin (NG) are phytochemicals possessing antioxidant properties and estrogenic activity. This study was conducted to investigate the toxicity of NP and the mitigating effects of RES and NG on NP toxicity in rats. Thirty male rats were classified into 5 groups as follows: 1- Normal control (NC), 2- Dimethyl sulfoxide (DMSO) group, 3- NP group, 4- NP + RES and 5- NP + NG. Results revealed that NP treatment significantly decreased the activities of superoxide dismutase, Catalase, Glutathione peroxidase and Glutathione content in blood, liver and kidney compared to NC and DMSO groups. Conversely, activity of Glutathione-s-transferase was significantly elevated in blood and decreased in liver and kidney. Moreover, significant escalation was observed in the levels of Malondialdehyde. Also, NP treatment led to a significant decrease in serum total testosterone and testis weight, accompanied with concurrent elevation in estradiol level compared to NC and DMSO groups. All the recorded effects induced by NP treatment were effectively countered by co-treatment with RES or NG. In addition, molecular docking studies were carried out to reveal the interactions between NP, RES, NG and estrogen receptor beta which provide a possible mechanism for their potential estrogenic activity. Overall, our study gives a deeper understanding of the toxic effect of NP on antioxidant capacity and endocrine functions as well as the potential therapeutic utility of RES and NG in alleviating these adverse effects.